رأس المال النفسي الإيجابي وعلاقته بأساليب المواجهة لدى طلبة الجامعة - محاسنة، أحمد محمد موسى; العظامات، عمر عطا الله علي; عبود، محمد هاني محمد; شيشاني، إنعام شاهر (جامعة البحرين - مركز النشر العلمي, 2022)
هدفت الدراسة الحالية إلى فحص العلاقة الارتباطية بين رأس المال النفسي الإيجابي وأساليب المواجهة، كما هدفت إلى معرفة مستوى رأس المال النفسي الإيجابي، ومعرفة أكثر أساليب المواجهة استخداما، ومعرفة فيما إذا كان هنالك فروق في رأس المال النفسي الإيجابي، وأساليب المواجهة تعزى لمتغيري الجنس، والتخصص الأكاديمي. ولغايات جمع البيانات والمعلومات، استخدم مقياس رأس المال النفسي الإيجابي، ومقياس أساليب المواجهة. تكونت عينة الدراسة من (830) طالبا وطالبة من طلبة الجامعة الهاشمية تم اختيارهم بالطريقة القصدية. وأظهرت النتائج أن مستوى رأس المال النفسي الإيجابي جاء بمستوى مرتفع، ووجود فروق دالة إحصائيا في مستوى رأس المال النفسي الإيجابي تعزى لمتغير الجنس، ولصالح الذكور. ووجود فروق دالة إحصائيا في مستوى رأس المال النفسي الإيجابي تعزى لمتغير التخصص الأكاديمي، ولصالح طلبة الكليات الإنسانية. فيما أظهرت النتائج أن أساليب المواجهة الفعالة هي الأكثر استخداما، ووجود فروق دالة إحصائيا في أساليب المواجهة الفعالة تعزى لمتغير الجنس، ولصالح الذكور. وأخيرا أظهرت النتائج وجود علاقة ارتباطية موجبة (ر = 0.26) ودالة إحصائيا عند مستوى دلالة (α=0.05) بين رأس المال النفسي الإيجابي وأبعاده (الفعالية الذاتية، الأمل، المرونة، التفاؤل) وأساليب المواجهة الفعالة، ووجود علاقة ارتباطية سالبة (ر= -0.025) ودالة إحصائيا عند مستوى دلالة (α=0.05) بين رأس المال النفسي الإيجابي وأبعاده (الفعالية الذاتية، الأمل، المرونة، التفاؤل) وأساليب المواجهة غير الفعالة. The current study aimed to investigate the relationship between positive psychological capital and coping styles; it also aimed to identify the level of the positive psychological capital; the most coping styles used. Furthermore, it also identified whether there are statistically significant differences in the level of positive psychological capital and the coping styles due to gender and academic specialization variables. To achieve the aims of the study, the researchers used the positive psychological capital scale and the coping styles scale. The study sample consisted of (830) students at the Hashemite University who were chosen using the convenience method. The results of the study showed that the level of positive psychological capital was higher and showed statistically significant differences in the level of positive psychological capital due to gender which showed a higher rate for the male gender other than female gender variables; it also showed that there were statistically significant differences in the level of positive psychological capital due to academic specialization, in favour of students majoring in humanities. However, the results showed that the effective coping styles are the most widely used, and there were statistically significant differences in the effective coping style due to gender which showed a higher rate for the male gender other than female gender variables. Finally, the findings showed a positive correlation (r=0.26) and statistically significant (α=0.05) between positive psychological capital and its subscales (self-efficacy, hope, resilience, and optimism) and effective coping style. The current research findings also showed a negative correlation (r=-0.25) and statistically significant (α=0.05) between positive psychological capital and its subscales (self efficacy, hope, resilience, and optimism) and non-effective coping style.
Keywords: علم النفس التربوي -- الصحة النفسية -- طلبة الجامعات -- الضغوط الأكاديمية